Overcoming E-Government Challenges through Insights from Simple Apps - Alvina Dea Ervinda; Ilmi Usrotin Choiriyah (Universitas Muhammadiyah Sidoarjo, 2024)
This study explores the development strategy for e-government preparation through Simple Applications at the Sidoarjo Regency Community and Village Empowerment Service in East Java, Indonesia. Using qualitative descriptive methods, data was collected through observation, interviews, and documentation from key personnel involved in managing the Simple Application. Findings highlight successful implementation alongside challenges such as a lack of IT expertise among staff and inadequate infrastructure for effective socialization efforts. These obstacles necessitate improvements in human resources and infrastructure to sustain and expand e-government benefits across the region, promoting enhanced governmental transparency and service delivery. Highlights: Successful e-government with Simple Applications in Sidoarjo Regency. Challenges: lack of IT expertise, inadequate socialization infrastructure. Recommendations: improve human resources, enhance infrastructure for sustainable e-government. Keywords: e-government, Simple Application, community empowerment, infrastructure challenges, human resource development